PENERAPAN METODE INQUIRY MELALUI KEGIATAN PENJELAJAHAN UNTUK MENINGKATKAN HASIL BELAJAR - ., Asmu'i (INVENTA: Jurnal Pendidikan Guru Sekolah Dasar, 2019)
5 Grade students of Public Elementary School 4 Sepanjang Gondanglegi Malang in the 2016/2017 Academic Year need learning activities by utilizing the environment as a source of learning. One of the activities that can be done is in the form of walking exploration followed by play and adventure. Considering this, then on this occasion the researchers tried to apply the inquiry method through exploration activities as an effort to improve learning outcomes Physical, Sports and Health Education. Based on the results of observations that have been made, it can be seen that the skills of 5 Grade students of Public Elementary School 4 Sepanjang have increased after applying the inquiry method through exploration activities, this is indicated by the researcher’s assessment of student activity in seeking information, the pleasure shown by students, and team/group collaboration. If at first the average results of the assessment in Cycle I amounted to 62.4, then the implementation of Cycle II achieved an average score of 77.9. In addition, with the implementation of the Inquiry method through exploration activities around the school in Physical Education, Sports and Health subjects in 5 Grade students of Public Elementary School 4 Sepanjang, it can be seen that there is a significant increase in student learning achievement, this is as shown in the value of student evaluation. If in Cycle I the number of evaluation values ​​achieved is still equal to 1770 with a percentage of learning completeness of 39.29%, then in Cycle II it has improved considerably, until it reaches an evaluation value of 2450 with a percentage of learning completeness of 100.00%